Kualitas Patty Burger Menggunakan Jantung Pisang Batu (Musa balbisiana colla) Sebagai Bahan Pengganti Daging - Ida Ayu Kalpikawati; Ngakan Putu Sudiarta (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
This study aims to determine the quality of patty burger using the inflorescence of banana (Musa balbisiana Colla) as a meat substitute. This research is an experimenta research. The experimental stage is processing the inflorescence of banana into a meat substitute for the patty burger based on a modified standard recipe to get a product that meets the standard patty burger. The results of the patty burger products were then tested for quality using organoleptic tests including the characteristics of aroma, taste, texture and color. Laboratory tests were carried out to determine the fat content of the patty burger. The results showed that the average value of the panelists' assessment on the organoleptic test was 81%, categorized as very good criteria. The test on the fat content of the patty burger obtained an average value of 18.25%. This results indicate that the inflorescence of banana (Musa balbisiana Colla) can be used as a substitute for meat in patty burger.